2021
DOI: 10.31234/osf.io/cj3xq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflated false-positive risk in common regression analyses: A combinatorial analysis of model sets

Abstract: Even with a small number of variables researchers can test many possible models of their data thus increasing the risk of false-positive results. Using combinatorics, we show that one key independent variable and three covariates can generate 95 possible models, while six covariates can generate over 2.3 million models. Such large model sets nearly guarantee false-positive results. Using simulation, we show that preregistering a single analysis with a key independent variable heavily reduces the risk of false-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Indeed, a sample of 150 nutritional epidemiology studies found that 94% did not report a priori covariate selection, and only 20% reported the selection criteria for all covariates (17). Simulations have shown that flexibility in covariate selection can increase the chance of achieving statistical significance (10,(41)(42)(43)(44). Together, the lack of a theoretical framework for any of our varied models raises the question of where on the HR distribution a true causal association may reside.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a sample of 150 nutritional epidemiology studies found that 94% did not report a priori covariate selection, and only 20% reported the selection criteria for all covariates (17). Simulations have shown that flexibility in covariate selection can increase the chance of achieving statistical significance (10,(41)(42)(43)(44). Together, the lack of a theoretical framework for any of our varied models raises the question of where on the HR distribution a true causal association may reside.…”
Section: Discussionmentioning
confidence: 99%